IDDF2019-ABS-0134 Sofosbuvir/velpatasvir is effective and safe in patients with concomitant proton pump inhibitor use in clinical studies. (June 2019) - Esteban, Rafael; Agarwal, Kosh; Calleja, Jose Luis; Dufour, Jean-Francois; Flamm, Steven; Gordon, Stuart; Stamm, Luisa; Ni, Liyun; Brainard, Diana; Sze Man Yip, Christina; Kowdley, Kris; Cooper, Curtis; et al.
Abstract : Background: Prior to the availability of Phase 1 drug interaction data, concomitant proton pump inhibitor (PPI) use was prohibited in clinical trials of sofosbuvir/velpatasvir (SOF/VEL). Later clinical studies allowed for the use of up to 20 mg omeprazole or equivalent dosing. This analysis evaluated the efficacy and safety of patients with and without compensated cirrhosis who received SOF/VEL for 12 weeks and reported concomitant use of a PPI. Methods: This was a retrospective analysis from 12 Phase 2 and Phase 3 clinical studies in which patients of all genotypes with and without compensated cirrhosis received 12 weeks of SOF/VEL and reported concomitant use of a PPI. Efficacy was assessed by SVR12 and relapse rates and safety was assessed by treatment-emergent adverse events (AEs). Results: 87 patients reported concomitant use of a PPI. The mean age (range) was 57 years (26–78), 79% were male and 75% white; 56% of patients were infected with genotype 3 and 29% with genotype 1; 37% of patients had compensated cirrhosis and 39% were treatment experienced. The most common PPI was omeprazole reported by 68% of patients. The SVR12 rate was 97% (84 of 87 patients). Of the 3 patients who did not achieve SVR12, 2 patients relapsed (relapse rate 2%) and one patient with a history of diabetes discontinued SOF/VEL after 7 days of dosing due to hyperglycemia. No other patient had an AE which led to discontinuation or interruption of SOF/VEL. 78% of patients had an AE, most of which were mild, and 11% had a serious AE. These efficacy and safety are comparable to patients enrolled in the same studies who received SOF/VEL for 12 weeks without concomitant use of a PPI (SVR12 rate 97% [2445 of 2517 patients]; relapse rate 2% [40 of 2488 patients]). Conclusions: In Phase 2 and Phase 3 clinical studies, the single-tablet regimen of SOF/VEL for 12 weeks was effective and safe in patients with concomitant PPI use. These data support the use of SOF/VEL according to labeled recommendations with respect to co-administration of PPIs and other acid reducing agents.